2022
DOI: 10.1557/s43578-022-00712-0
|View full text |Cite
|
Sign up to set email alerts
|

Review on magnetocaloric high-entropy alloys: Design and analysis methods

Abstract: The search for high-performance functional alloys with improved service life and reliability entails the optimization of their mechanical properties. Recently, the high-entropy alloy (HEA) design concept has found new alloys with excellent mechanical properties. It utilizes multiprincipal elements to yield high configurational entropy of mixing, entailing a large compositional freedom with wide window of opportunities for property exploration. Their functional properties are usually modest when compared to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, there are relatively few researches on functional HEAs materials, especially magnetic functional HEAs. [19,20] In the early stages of HEAs research, it mainly…”
Section: Introductionmentioning
confidence: 99%
“…However, there are relatively few researches on functional HEAs materials, especially magnetic functional HEAs. [19,20] In the early stages of HEAs research, it mainly…”
Section: Introductionmentioning
confidence: 99%
“…A number of materials have been investigated for magnetocaloric refrigeration across different temperature ranges. [57][58][59] For example, La(FeSi) 13 [60] displays a temperature change of 6.9 K at an operating temperature of 190 K, while Mn 3 GaC [61] exhibits a temperature variation of 4.5 K at 163 K, and Gd 2 Si 2 Ge 2 [62] has a temperature change of 4.9 K at 262 K under an applied magnetic field of 2 T. These materials exhibit the most significant temperature change at the phase-transition temperature, and their operating range and cooling capacity depend on the width and characteristics of their magnetic phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] While the research of HEAs mainly focuses on the structural and mechanical properties, the magnetic properties of HEAs are still far from being fully understood. [17,18] Recently, RE-based HEAs (RE-HEAs) with a hexagonal structure have shown high magnetocaloric performance due to their large values of the magnetic entropy change. [19][20][21] For instance, as reported by Yuan et al, [22] the jΔS pk M j and RC values of the GdTbDyHoEr HEA can reach 8.6 J kg À1 K À1 and 627 J kg À1 under 5 T. For the GdTbHoErY HEA, Lu et al [23] showed a jΔS pk M j value of 5.4 J kg À1 K À1 and a RC value of 453 J kg À1 .…”
Section: Introductionmentioning
confidence: 99%